Schiff base metal complexes as a dual antioxidant and antimicrobial agents - Racheal O. Awolope, Ikechukwu P. Ejidike,, Hadley S. Clayton (Journal of Applied Pharmaceutical Science, 2023)
The use of conventional antibiotics as both preventive and curative measures for antimicrobial infections has increased multidrug-resistant infections that have negatively impacted humans. Thus, better antimicrobial agents are needed. We investigated for the first time the antimicrobial and antioxidant activities of the 4,4’-{ethane-1,2- diylbis[nitrilo(Z)methylylidene]}bis(2-methoxyphenol) ligand (SV) and its metal complexes represented as CoSV, CuSV, NiSV, ZrOSV, VOSV, and UO2SV. The complexes were characterized using different spectroscopic techniques, such as Fourier transform infrared, UV absorption spectra, and elemental analysis. The antibacterial properties of the complexes were evaluated using standard methods. The results showed that all the complexes exhibited strong to moderate activities against Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumonia, and Pseudomonas aeruginosa compared to the parent ligand alone. Increased antibacterial properties of the complexes were attributed to the increased lipophilic nature of the ligand upon coordination with metal. The IC50 (μg/ml) value of the 2,2-diphenyl- 1-picrylhydrazyl radical scavenging activities of the Schiff base metal complexes ranged from 3.24 to 6.44, which was higher than that of standard ascorbic acid [IC50 (μg/ml) = 1.22] or gallic acid [IC50 (μg/ml) = 2.02] used. The strong antibacterial properties and pronounced radical scavenging activities show that the complexes could be promising alternatives as antibacterial and antioxidant agents.